Preparation method of diamond / aluminum composite material
The preparation of diamond/aluminum composite materials by ball mill mixing and pneumatic impregnation methods has solved the problem of difficult control of diamond content in the prior art, and the regulation of high density and thermal conductivity of the material is achieved, which reduces processing difficulty and cost.
Patent Information
- Application Number
- CN202510057911.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-01-14
AI Technical Summary
The diamond content in the existing liquid phase method is high and difficult to control, resulting in high mechanical processing, high cost and performance that does not meet the requirements of different application scenarios.
Mix aluminum powder and diamond powder by ball mill, fill it into a graphite mold, and heat it above the melting point of the aluminum in a gas pressure immersion furnace. Pressure is used to make the molten aluminum liquid penetrate into the gap of the mixed powder, control the interface reaction between aluminum and diamond, and regulate the volume fraction of the diamond.
The precise control of diamond content in diamond/aluminum composite materials is achieved, reducing the difficulty and cost of the material's mechanical processing, and improving the surface weldability and thermal conductivity of the composite materials.
Smart Images

Figure CN119910161A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite materials, and in particular relates to a method for preparing a diamond / aluminum composite material. The method can regulate the diamond content in the diamond / aluminum composite material. Background Art
[0002] With the rapid development of electronic information technology and micro-nano manufacturing technology, the characteristic size of electronic components has been reduced to the micro-nano level. The high integration and high power of electronic components have made heat dissipation the main bottleneck restricting the development of electronic devices. Therefore, the development of high-performance thermal management materials has become an important driving force for the development of the electronic information industry. Diamond / aluminum composite materials are a research hotspot for the new generation of thermal management materials due to their excellent thermophysical properties, good mechanical properties and low density.
[0003] The diamond / aluminum composites prepared by liquid phase method have the advantages of high density and easy control of interfacial reaction. The density and thermal conductivity of diamond / aluminum composites prepared by gas pressure infiltration method are as high as 99.2% and 1021 W / mK respectively (N. Li et al. Mater. Today Phys. 28 (2022) 100901), which has good application prospects. However, due to the natural stacking of diamond powder, the volume fraction of diamond in the diamond / aluminum composite prepared by liquid phase method is usually above 50% (WB Johnson, J. Mater. Res. 8 (1993) 1169-1173 (pressureless infiltration); PW Ruch et al. Compos. Sci. Technol. 66 (2006) 2677-2685 (pressure infiltration); IE Monje et al. Compos. Part A 48 (2013) 9-14 (gas pressure infiltration)), and it is difficult to change the diamond content in a large range by adjusting the stacking method of diamond powder. Due to the addition of diamond superhard phase, the mechanical processing and welding processing of high volume fraction diamond / aluminum composite materials are greatly limited. The high price of diamond powder is also one of the main reasons why diamond / aluminum composite materials are difficult to apply on a large scale. Although diamond / aluminum composite materials with high thermal conductivity can be obtained by adding high volume fraction diamond, different application scenarios have different requirements for the thermal conductivity of diamond / aluminum composite materials. Adding excessive diamond powder sometimes leads to excess performance and increased costs.
[0004] In order to overcome the defect that the diamond content in the diamond / aluminum composite material prepared by the existing liquid phase method is high and uncontrollable, the present invention provides a preparation method of the diamond / aluminum composite material, which can control the diamond content in the diamond / aluminum composite material according to actual application requirements.
[0005] The present invention provides a method for preparing a diamond / aluminum composite material, comprising the following steps:
[0006] 1) Weighing aluminum powder and diamond powder, and then ball milling to obtain mixed powder;
[0007] 2) filling the mixed powder obtained in step 1) into a graphite mold with a gate, then placing the graphite mold filled with the mixed powder in a gas pressure infiltration furnace, and placing an aluminum block above the graphite mold;
[0008] 3) After the pressure infiltration furnace is evacuated, the graphite mold containing the mixed powder and the aluminum block in step 2) are heated to a temperature above the melting point of the aluminum block, and the aluminum block is melted;
[0009] 4) Use inert gas to increase the pressure in the gas pressure infiltration furnace, so that the molten aluminum liquid can penetrate into the gap between the mixed powders through the graphite mold gate under pressure, and keep the temperature and pressure of the gas pressure infiltration furnace to control the interface reaction between aluminum and diamond;
[0010] 5) stopping heating and cooling to room temperature with the furnace to obtain the diamond / aluminum composite material.
[0011] Preferably, in step 1), the mass ratio of the aluminum powder to the diamond powder is (0.1-10):1, and the total mass of the aluminum powder and the diamond powder is 10-500 g. In the existing liquid phase method for preparing diamond / aluminum composite materials, aluminum powder is usually not mixed into the diamond powder. The present invention can control the temperature of the graphite mold filled with aluminum / diamond powder to be below the melting point of the aluminum powder, does not affect the subsequent molten aluminum liquid infiltrating the gap of the mixed powder, and can reduce the amount of diamond added to 10%.
[0012] Preferably, in step 1), the particle size of the aluminum powder is 10-500 μm, and the particle size of the diamond powder is 50-700 μm. The diamond powder can be uncoated diamond powder or metal-coated diamond powder.
[0013] Preferably, in step 1), the ball milling time is 5 to 60 minutes, and the ball milling speed is 50 to 200 rpm.
[0014] Preferably, in step 2), the material of the aluminum block is selected from one of pure aluminum, aluminum silicon alloy, 1050 aluminum alloy and 1100 aluminum alloy. The mass of the aluminum block is 50-1000 g, and the volume of the aluminum block is 5-20 times the volume of the graphite mold. The excess aluminum liquid cannot enter the interior of the graphite mold and remains above the mold. When the reaction is completed, the volume of the diamond / aluminum composite material in the graphite mold shrinks during the cooling process. The molten aluminum liquid above the graphite mold can continue to enter the graphite mold through the gate. This part of the excess aluminum liquid can reduce the shrinkage cavities in the diamond / aluminum composite material and improve the density of the diamond / aluminum composite material.
[0015] Preferably, in step 2), the graphite mold is made of high-purity graphite, the diameter of the gate above the graphite mold is 3-10 mm, and the distribution density is 2-5 / cm 2 .
[0016] Preferably, in step 3), the air pressure infiltration furnace is evacuated to a vacuum degree of ≤1 Pa. The heating rate of the aluminum block is 10-50 °C / min, the heating temperature is 600-1000 °C, and the holding time is 5-60 minutes. More preferably, the heating temperature is 50 °C to 1000 °C higher than the melting point of the aluminum block. It should be noted that in the melting process of the aluminum block above the mold in step 3), the aluminum powder in the graphite mold cannot be melted, otherwise the aluminum liquid cannot enter the gap between the aluminum / diamond mixed powder in the graphite mold during the pressurization process in step 4). A heating component (such as a resistance wire) can be set at the upper part of the furnace chamber of the air pressure infiltration furnace so that the heating component heats the aluminum block, and the temperature of the graphite mold located below the aluminum block is relatively low. In this way, the aluminum block can be melted without melting the aluminum powder.
[0017] Preferably, in step 4), the inert gas is one of nitrogen and argon, the pressure of the gas pressure infiltration furnace after pressurization is 0.3-3 MPa, and the heat preservation and pressure holding time is 5-60 minutes. During the pressure holding period, the aluminum liquid contacts the diamond and an interface reaction occurs to form a compact structure, thereby improving the density of the diamond / aluminum composite material. The time of the interface reaction can be controlled by controlling the heat preservation and pressure holding time.
[0018] The present invention also provides a diamond / aluminum composite material prepared by the method, wherein the volume fraction of diamond in the diamond / aluminum composite material is 10-70%.
[0019] The present invention also provides a device for implementing the method, comprising a graphite mold, an aluminum block and a gas pressure infiltration furnace. The graphite mold is a fully enclosed structure, with a plurality of gates on the top, and the graphite mold is filled with aluminum powder and diamond powder; the aluminum block is placed above the graphite mold, and the graphite mold and the aluminum block are placed together in the furnace chamber of the gas pressure infiltration furnace; a heating resistance wire is provided on the upper part of the furnace chamber, and the heating resistance wire and the aluminum block are located at the same height.
[0020] The present invention has the following beneficial effects:
[0021] The present invention adopts a liquid phase method to prepare a diamond / aluminum composite material, and by controlling the diamond content in the diamond / aluminum mixed powder, the diamond content in the prepared diamond / aluminum composite material can be accurately controlled. The present invention can prepare a diamond / aluminum composite material with a diamond volume fraction of 10-70% and a density higher than 99%, and at the same time, the thermal conductivity of the diamond / aluminum composite material can be regulated within a wide performance range of 300-800 W / mK. The present invention can reduce the mechanical processing difficulty and material cost of the diamond / aluminum composite material, and at the same time improve the surface weldability of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0023] Figure 1 A schematic diagram of a device used in the method for preparing the diamond / aluminum composite material of the present invention;
[0024] Among them, 1-graphite mold; 11-gate; 12-aluminum powder; 13-diamond powder; 2-aluminum block; 3-air pressure infiltration furnace; 31-heating resistance wire.
[0025] Figure 2 This is a surface morphology of the diamond / aluminum composite material prepared in Example 1 of the present invention;
[0026] Figure 3 This is a surface morphology of the diamond / aluminum composite material prepared in Example 2 of the present invention;
[0027] Figure 4 This is a surface morphology of the diamond / aluminum composite material prepared in Comparative Example 1 of the present invention;
[0028] Figure 5 This is a surface morphology of the diamond / aluminum composite material prepared in Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0029] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.
[0030] Figure 1The present invention is a schematic diagram of a device used in the method for preparing the diamond / aluminum composite material, wherein the device comprises a graphite mold 1, an aluminum block 2 and a gas pressure infiltration furnace 3. The graphite mold 1 is a fully enclosed structure, and a plurality of gates 11 are provided on the top thereof. The graphite mold 1 is filled with aluminum powder 12 and diamond powder 13. The aluminum block 2 is placed above the graphite mold 1, and the graphite mold 1 and the aluminum block 2 are placed together in the furnace chamber of the gas pressure infiltration furnace 3. A heating resistance wire 31 is provided at the upper part of the furnace chamber, and the heating resistance wire 31 is at the same height as the aluminum block 2, so that after the heating is turned on, the aluminum block 2 is heated and melted, while the temperature of the graphite mold 1 is relatively low, and the aluminum powder therein does not melt.
[0031] The present invention provides a method for preparing a diamond / aluminum composite material, comprising the following steps:
[0032] 1) Weighing aluminum powder and diamond powder, and then ball milling to obtain mixed powder;
[0033] 2) filling the mixed powder obtained in step 1) into a graphite mold with a gate, then placing the graphite mold filled with the mixed powder in a gas pressure infiltration furnace, and placing an aluminum block of a certain mass above the graphite mold;
[0034] 3) After the gas pressure infiltration furnace is evacuated, the gas pressure infiltration furnace heats the graphite mold and the aluminum block in the furnace cavity through the heating resistance wire. When the heating temperature reaches above the melting point of aluminum or aluminum alloy, the aluminum block melts;
[0035] 4) Use inert gas to increase the pressure in the gas pressure infiltration furnace, and control the temperature of the graphite mold filled with aluminum / diamond powder below the melting point of aluminum powder, so that the molten aluminum liquid can penetrate into the gap of the mixed powder through the graphite mold gate under pressure, and keep the temperature and pressure of the gas pressure infiltration furnace to control the interface reaction between aluminum and diamond;
[0036] 5) Stop heating and cool the furnace to room temperature. The volume of the diamond / aluminum composite material in the graphite mold shrinks during the cooling process. The molten aluminum above the graphite mold can continue to enter the graphite mold through the gate to increase the density of the composite material, thereby obtaining the diamond / aluminum composite material.
[0037] The present invention controls the volume fraction of diamond in the prepared diamond / aluminum composite material by controlling the content of diamond in the diamond / aluminum mixed powder, which can effectively reduce the mechanical processing difficulty and material cost of the diamond / aluminum composite material and improve the surface weldability of the composite material.
[0038] In order to better understand the present invention, specific examples are described in detail below. It should be noted that the following examples are only used to explain the present invention and are not intended to limit the scope of the present invention.
[0039] Example 1
[0040] Step 1, weigh 60 g of aluminum powder with a particle size of 80 μm and 40 g of diamond powder with a particle size of 120 μm and a surface coated with a metal zirconium coating;
[0041] Step 2: Use a ball mill to mix aluminum powder and diamond powder. The mixing time is 15 minutes and the ball milling speed is 60 rpm.
[0042] Step 3: Fill the powder mixed by ball milling in step 2) into a graphite mold with a gate. The diameter of the gate above the graphite mold is 3 mm and the distribution density is 5 / cm 2 , then put the graphite mold filled with the mixed powder into a gas pressure infiltration furnace, and place an Al-12wt.%Si alloy block with a mass of 100 g on top of the graphite mold;
[0043] Step 4: evacuate the pressure impregnation furnace to a vacuum degree of 0.1 Pa;
[0044] Step 5: Heat the graphite mold and aluminum block containing the mixed powder in step 3) to 650°C at a heating rate of 30°C / min;
[0045] Step 6: Use argon gas to increase the pressure in the pressure infiltration furnace to 0.5 MPa, and infiltrate the molten aluminum liquid into the gaps of the mixed powder through the graphite mold gate under pressure;
[0046] Step 7: Maintain the temperature and pressure in the gas pressure infiltration furnace for 10 minutes to control the interface reaction between aluminum and diamond;
[0047] Step 8: Stop heating and cool to room temperature in the furnace to obtain a diamond / aluminum composite material. Figure 2 The surface morphology of the diamond / aluminum composite material prepared in Example 1 shows that the diamond is evenly distributed in the aluminum matrix. The volume fraction of diamond is 10%, the thermal conductivity is 304 W / mK, and the density is 99% as measured by the Archimedean drainage method combined with the mixing law.
[0048] Example 2
[0049] Step 1, weighing 20 g of aluminum powder with a particle size of 80 μm and 20 g of diamond powder with a particle size of 270 μm and a surface coated with a metal titanium coating;
[0050] Step 2: Use a ball mill to mix aluminum powder and diamond powder. The mixing time is 15 minutes and the ball milling speed is 60 rpm.
[0051] Step 3: Fill the powder mixed by ball milling in step 2) into a graphite mold with a gate. The diameter of the gate above the graphite mold is 4 mm and the distribution density is 4 / cm 2, then put the graphite mold filled with the mixed powder into a gas pressure infiltration furnace, and place a pure aluminum block with a mass of 70 g on top of the graphite mold;
[0052] Step 4: evacuate the pressure impregnation furnace to a vacuum degree of 0.1 Pa;
[0053] Step 5: heating the graphite mold and aluminum block containing the mixed powder in step 3) to 800°C at a heating rate of 30°C / min;
[0054] Step 6: Use argon gas to increase the pressure in the pressure infiltration furnace to 1 MPa, and infiltrate the molten aluminum liquid into the gaps of the mixed powder through the graphite mold gate under pressure;
[0055] Step 7: Maintain the temperature and pressure in the gas pressure infiltration furnace for 20 minutes to control the interface reaction between aluminum and diamond;
[0056] Step 8: Stop heating and cool to room temperature in the furnace to obtain a diamond / aluminum composite material. Figure 3 The surface morphology of the diamond / aluminum composite material prepared in Example 2 was tested by the Archimedean drainage method combined with the law of mixing, and the volume fraction of diamond was 23%, the thermal conductivity was 320 W / mK, and the density was 99.1%.
[0057] Example 3
[0058] Step 1: weigh 4 g of aluminum powder with a particle size of 80 μm and 12 g of diamond powder with a particle size of 270 μm;
[0059] Step 2: Use a ball mill to mix aluminum powder and diamond powder. The mixing time is 15 minutes and the ball milling speed is 60 rpm.
[0060] Step 3: Fill the powder mixed by ball milling in step 2) into a graphite mold with a gate. The diameter of the gate above the graphite mold is 4 mm and the distribution density is 4 / cm 2 , then put the graphite mold filled with the mixed powder into a gas pressure infiltration furnace, and place a pure aluminum block with a mass of 50 g on top of the graphite mold;
[0061] Step 4: evacuate the pressure impregnation furnace to a vacuum degree of 0.1 Pa;
[0062] Step 5: heating the graphite mold and aluminum block containing the mixed powder in step 3) to 900°C at a heating rate of 30°C / min;
[0063] Step 6: Use argon gas to increase the pressure in the pressure infiltration furnace to 1 MPa, and infiltrate the molten aluminum liquid into the gaps of the mixed powder through the graphite mold gate under pressure;
[0064] Step 7: Maintain the temperature and pressure in the gas pressure infiltration furnace for 20 minutes to control the interface reaction between aluminum and diamond;
[0065] Step 8: Stop heating and cool to room temperature with the furnace to obtain a diamond / aluminum composite material. The volume fraction of diamond is 34%, the thermal conductivity is 354 W / mK, and the density is 99.1% through the Archimedean drainage method combined with the mixing law test.
[0066] Through Examples 1-3, the volume fraction of diamond in the composite material can be estimated based on the volume ratio of the diamond / aluminum mixed powder. The calculation formula is:
[0067] The volume fraction of diamond in the composite material = 50% × the volume content of diamond in the mixed powder.
[0068] Comparative Example 1
[0069] Step 1: Fill diamond powder with a particle size of 270 μm into a graphite mold with a gate. The diameter of the gate above the graphite mold is 4 mm, and the distribution density is 4 / cm 2 , then put the graphite mold filled with diamond powder in a gas pressure infiltration furnace, and place a pure aluminum block with a mass of 100 g on top of the graphite mold;
[0070] Step 4: evacuate the pressure impregnation furnace to a vacuum degree of 0.1 Pa;
[0071] Step 5: heating the graphite mold and aluminum block containing diamond powder in step 3) to 850°C at a heating rate of 30°C / min;
[0072] Step 6: Use argon gas to increase the pressure in the pressure infiltration furnace to 1.5 MPa, and infiltrate the molten aluminum liquid into the gaps of the diamond powder through the graphite mold gate under pressure;
[0073] Step 7: Maintain the temperature and pressure in the gas pressure infiltration furnace for 20 minutes to control the interface reaction between aluminum and diamond;
[0074] Step 8: Stop heating and cool to room temperature in the furnace to obtain a diamond / aluminum composite material. Figure 4 The surface morphology of the diamond / aluminum composite material prepared in this comparative example 1, wherein the diamond content is much higher than that in the embodiment. The volume fraction of diamond obtained by the Archimedean drainage method combined with the mixing law test is 53%, the thermal conductivity is 722 W / mK, and the density is 99.3%.
[0075] Comparative Example 2
[0076] Step 1: Fill diamond powder with a particle size of 70 μm into a graphite mold with a gate. The diameter of the gate above the graphite mold is 4 mm, and the distribution density is 4 / cm 2 , continuously vibrate the graphite mold until it can no longer be filled with diamond powder, then place the graphite mold filled with diamond powder in a gas pressure infiltration furnace, and place a pure aluminum block with a mass of 100 g on top of the graphite mold;
[0077] Step 4: evacuate the pressure impregnation furnace to a vacuum degree of 0.1 Pa;
[0078] Step 5: heating the graphite mold and aluminum block containing diamond powder in step 3) to 900°C at a heating rate of 50°C / min;
[0079] Step 6: Use argon gas to increase the pressure in the gas pressure infiltration furnace to 1 MPa, and infiltrate the molten aluminum liquid into the gaps of the diamond powder through the graphite mold gate under pressure;
[0080] Step 7: Maintain the temperature and pressure in the gas pressure infiltration furnace for 20 minutes to control the interface reaction between aluminum and diamond;
[0081] Step 8: Stop heating and cool to room temperature in the furnace to obtain a diamond / aluminum composite material. Figure 5 The surface morphology of the diamond / aluminum composite material prepared in this comparative example 2 was tested by the Archimedean drainage method combined with the mixing law to obtain a diamond volume fraction of 65%, a thermal conductivity of 498 W / mK, and a density of 99.1%.
[0082] Comparative Examples 1 and 2 show that if only diamond powder is added to the graphite mold, the diamond content in the obtained diamond / aluminum composite material is generally higher than 50%. Therefore, the diamond volume fraction of the diamond / aluminum composite material prepared in Examples 1, 2 and 3 is much lower than the diamond volume fraction of the diamond / aluminum composite material prepared in Comparative Examples 1 and 2, indicating that the present invention can effectively control the volume fraction of diamond in the diamond / aluminum composite material and reduce the material cost of the diamond / aluminum composite material.
[0083] Comparative Example 3
[0084] In step 3, no aluminum block was placed above the graphite mold, and the argon gas pressurization in step 6 was not performed. The other steps were the same as in Example 1. That is, no additional aluminum block was placed and pressurization was performed, and the graphite mold containing diamond powder and aluminum powder was directly heated. Since no aluminum liquid was added, the diamond / aluminum composite material could not be prepared, and the final mixed powder remained in its original state.
[0085] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing a diamond / aluminum composite material, characterized in that: The following steps are involved: 1) Weighing aluminum powder and diamond powder, and then ball milling to obtain mixed powder; 2) filling the mixed powder obtained in step 1) into a graphite mold with a gate, then placing the graphite mold filled with the mixed powder in a gas pressure infiltration furnace, and placing an aluminum block above the graphite mold; 3) After the pressure infiltration furnace is evacuated, the graphite mold containing the mixed powder and the aluminum block in step 2) are heated to a temperature above the melting point of the aluminum block, and the aluminum block is melted; 4) Use inert gas to increase the pressure in the gas pressure infiltration furnace, so that the molten aluminum liquid can penetrate into the gap between the mixed powders through the graphite mold gate under pressure, and keep the temperature and pressure of the gas pressure infiltration furnace to control the interface reaction between aluminum and diamond; 5) stopping heating and cooling to room temperature with the furnace to obtain the diamond / aluminum composite material.
2. The method for preparing the diamond / aluminum composite material according to claim 1, characterized in that: In step 1), the mass ratio of the aluminum powder to the diamond powder is (0.1-10):1, and the total mass of the aluminum powder and the diamond powder is 10-500 g.
3. The method for preparing the diamond / aluminum composite material according to claim 1, characterized in that: In step 1), the particle size of the aluminum powder is 10-500 μm, and the particle size of the diamond powder is 50-700 μm.
4. The method for preparing the diamond / aluminum composite material according to claim 1, characterized in that: In step 2), the material of the aluminum block is selected from one of pure aluminum, aluminum silicon alloy, 1050 aluminum alloy and 1100 aluminum alloy.
5. The method for preparing the diamond / aluminum composite material according to claim 4, characterized in that: In step 2), the mass of the aluminum block is 50-1000 g, and the volume of the aluminum block is 5-20 times the volume of the graphite mold.
6. The method for preparing the diamond / aluminum composite material according to claim 1, characterized in that: In step 2), the graphite mold is made of high-purity graphite, the diameter of the gate above the graphite mold is 3-10 mm, and the distribution density is 2-5 / cm 2 .
7. The method for preparing the diamond / aluminum composite material according to claim 1, characterized in that: In step 3), the pressure infiltration furnace is evacuated to a vacuum degree of ≤1 Pa, the aluminum block is heated at a rate of 10-50°C / min, the heating temperature is 600-1000°C, and the insulation time is 5-60 minutes.
8. The method for preparing the diamond / aluminum composite material according to claim 1, characterized in that: In step 4), the inert gas is one of nitrogen and argon, the pressure of the pressure infiltration furnace after pressurization is 0.3-3 MPa, and the heat and pressure holding time is 5-60 minutes.
9. The diamond / aluminum composite material prepared by the method according to any one of claims 1 to 8, characterized in that: The volume fraction of diamond in the diamond / aluminum composite material is 10-70%.
10. A device for implementing the method according to any one of claims 1 to 8, characterized in that: The device comprises a graphite mold, an aluminum block and a gas pressure infiltration furnace, wherein: The graphite mold is a fully enclosed structure with several gates on the top. The graphite mold is filled with aluminum powder and diamond powder. An aluminum block is placed above the graphite mold, and the graphite mold and the aluminum block are placed together in a furnace chamber of a gas pressure infiltration furnace; A heating resistance wire is arranged on the upper part of the furnace chamber, and the heating resistance wire and the aluminum block are located at the same height.
Citation Information
Patent Citations
Technological method of manufacturing diamond / aluminum composite material through pressure-free infiltration method
CN109777987A
High-heat-conductivity and high-reliability diamond / aluminum composite material and preparation technology thereof
CN110724845A
Low-cost preparation method of high-thermal-conductivity diamond reinforced metal matrix composite material
CN112981205A
Preparation method of diamond aluminum composite material
CN118563155A
Diamond / aluminum composite material with nano gradient interface and preparation method
CN118726926A